Lithological control of land subsidence induced by groundwater withdrawal in new urban AREAS (Granada Basin, SE Spain). Multiband DInSAR monitoring. Issue 13 (6th March 2016) - Notti, Davide; Mateos, Rosa María; Monserrat, Oriol; Devanthéry, Nùria; Peinado, Tomás; Roldán, Francisco Javier; Fernández‐Chacón, Francisca; Galve, Jorge Pedro; Lamas, Francisco; Azañón, Jose Miguel
Abstract: Ground subsidence in the southeastern border of the Granada Basin (SE Spain) has been studied using remote sensing techniques. Over the last decades, the region has experienced a huge urban expansion, which has caused a substantial increase in water supply requirements. Water needs are exclusively met by groundwater by means of numerous pumping wells, which exploit a confined detrital aquifer of alluvial fan deposits with a heterogeneous facies distribution. A general piezometric level decline (up to 50 m) has been recorded in the aquifer during the past 30 years that has induced the generation of a subsiding area with oval shape oriented WNW‐ESE just where the new urban areas and pumping wells are located. Subsidence has been monitored by exploiting synthetic aperture radar (SAR) images from ENVISAT (2003–2009) and Cosmo‐SkyMed (2011–2014). A new approach, which combines A‐DInSAR and small‐area persistent scatterer interferometry (PSI) analysis, has been applied obtaining a good accuracy regarding temporal and spatial dimension of the subsidence. ENVISAT data (2003–2009) reveal subsidence rates up to 10–15 mm/year, and Cosmo‐SkyMed (2011–2014) values slightly lower; up to 10 mm/year. Temporal variations in the subsidence velocity are in accordance with the rainfall pattern and piezometric fluctuations in the aquifer. The sector with highest rates of subsidence does not correspond to the area with more intense groundwater exploitation but to the area with greater presence of clays in the confining layer of the aquifer. There is a clear lithological control in the spatial distribution of the ground subsidence. This work integrates detailed geological and hydrogeological data with differential SAR interferometry monitoring with the aim to better understand subsidence processes in detrital aquifers with small‐scale heterogeneity. Copyright © 2016 John Wiley & Sons, Ltd.